2018
DOI: 10.1111/tmi.13154
|View full text |Cite
|
Sign up to set email alerts
|

Pain, balance, grip strength and gait parameters of older adults with and without post‐chikungunya chronic arthralgia

Abstract: Summary Objective To compare the levels of pain, grip strength, balance and gait in older adults with and without post‐Chikungunya chronic arthralgia (PCCA). Methods Sixty‐two older adults, 30 with and 32 without PCCA participated in the study. Pain level was assessed using a Visual Analogue Scale (VAS). Gait during a 10‐m walk was assessed using inertial sensors. Semi‐static balance was assessed during an eyes‐closed bipedal balance test on a force platform, and grip strength was assessed using a hand dynamom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
(75 reference statements)
0
13
2
Order By: Relevance
“…Terauchi et al [30], in a survey of middle-aged women, showed that a greater HGS was associated with lower muscle and joint pains (OR: 0.92; CI 95%: 0.87-0.97). Forechi et al [23] observed that patients with post-chikungunya chronic arthralgia had signi cantly lower HGS than adults without this disorder (P<0.001). Findings of a prospective study on young men showed that decreased muscle strength was not associated with an increased risk of fracture musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terauchi et al [30], in a survey of middle-aged women, showed that a greater HGS was associated with lower muscle and joint pains (OR: 0.92; CI 95%: 0.87-0.97). Forechi et al [23] observed that patients with post-chikungunya chronic arthralgia had signi cantly lower HGS than adults without this disorder (P<0.001). Findings of a prospective study on young men showed that decreased muscle strength was not associated with an increased risk of fracture musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of musculoskeletal pain in men is lower than women, men are affected by comorbidities associated with these chronic pains as well, leading them to risky behaviors to suppress pain, such as the use of narcotic drugs [22]. Low muscle strength can predict frailty, sarcopenia, falls, fractures, and overall reduced quality of life [12,23]. HGS is a valid and reliable method for determining the maximum hand muscle strength that re ects overall muscle strength and nutritional status [24].…”
Section: Discussionmentioning
confidence: 99%
“…Results published in [140] show that it is possible to discriminate patients with complex regional pain syndrome from control subjects using a small set of gait characteristics extracted from accelerometer data during a short set of physical performance tests [170]. In [24], gait using inertial sensors was analyzed in adult subjects with chronic arthralgia after Chikungunya virus infection, finding a correlation of pain with alterations in gait, grip strength and balance.…”
Section: Physical Activity As a Pain Indexmentioning
confidence: 99%
“…More studies are needed to analyze the effects of treatments and interventions on pain, as well as their functional manifestations, which would allow to optimize physical and clinical interventions on patients suffering from pain [24]. For this purpose, the integration of the information from these monitoring systems with the health systems in a standardized manner is necessary and remains a challenge for researchers and developers [301].…”
Section: Future Trends and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation